2018
DOI: 10.1016/j.avsg.2017.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Atherectomy-Associated Complications in the Southern California Vascular Outcomes Improvement Collaborative

Abstract: Increased treatment length is associated with an increased risk of atherectomy-associated complications. Demographic factors and comorbidities were not predictors of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Another retrospective study with 2048 peripheral vascular interventions (PVI) procedures was performed to determine the practice patterns of atherectomy for PVI in the Southern California Vascular Outcomes Improvement Collaborative (So Cal VOICe). 37 The rate of perforation was 2% in the atherectomy group and 2% in the no atherectomy group. Although the perforation rates in our meta-analysis showed an increasing trend in the atherectomy plus DCB group, the difference was not statistically significant compared with DCB only group (1.75% vs. 0.34%, RR: 2.04, 95%CI: 0.43-9.71, P ¼ 0.37).…”
Section: Discussionmentioning
confidence: 90%
“…Another retrospective study with 2048 peripheral vascular interventions (PVI) procedures was performed to determine the practice patterns of atherectomy for PVI in the Southern California Vascular Outcomes Improvement Collaborative (So Cal VOICe). 37 The rate of perforation was 2% in the atherectomy group and 2% in the no atherectomy group. Although the perforation rates in our meta-analysis showed an increasing trend in the atherectomy plus DCB group, the difference was not statistically significant compared with DCB only group (1.75% vs. 0.34%, RR: 2.04, 95%CI: 0.43-9.71, P ¼ 0.37).…”
Section: Discussionmentioning
confidence: 90%
“…In a multicenter study, 1-cm increase in lesion length brought two percent increased risk of atherectomy associated complications, and atherectomy was found to be related with increased risk of dissection. 23 In RESILIENT trial, stents were needed in 40.3% of the balloon angioplasty group, and it was found that longer lesions needed stent implantations. 1 Taking into consideration that the mean length of the current study was longer than the above-mentioned studies, it is not surprising to observe these rates of FLD and stent need.…”
Section: Discussionmentioning
confidence: 99%
“…죽종제거술과 관련된 합병증 발생은 병변의 길이가 길어질수록 유의미하게 증가한다고 보고되고 있으며( 37 ) 그 종류는 혈관 박리, 파열, 가성동맥류 형성, 원위 색전 등 기존의 PTA와 대동소이하다.…”
Section: 죽종제거술의 합병증과 한계unclassified